Interrelationships between sleep quality, circadian phase and rapid eye movement sleep: Deriving chronotype from sleep architecture - G. Horváth, Csenge; Schneider, Bence; Rozner, Borbála; Koczur, Míra; Bódizs, Róbert (Behavior research methods, 2025)
The relationship between sleep quality, circadian rhythms, and REM sleep has not been deliberately investigated in previous scientific reports. Here, we aim to examine the associations between these factors by specifically focusing on the temporal dynamics of REM sleep in all night records, as well as to provide a new, objective, EEG-derived chronotype indicator. To achieve those aims, a wearable EEG headband recorded home sleep database was analyzed in terms of total sleep time (TST), REM dynamics, core body temperature, wrist actigraphy, Munich Chronotype Questionnaire, Pittsburgh Sleep Quality Index, subjective morning sleep quality, and Likert Sleepiness Scale. Furthermore, records from the Budapest-Munich database of polysomnography (PSG) were analyzed for REM sleep patterns, TST, arousal dynamics, and age. The results show that the timing of the crest of REM propensity (REM maxprop ) reliably correlated with weekly average actigraphy sleep midpoints, subjective chronotype measures, and also tended to be associated with core body temperature. Additionally, REM maxprop emerged at earlier times in children and middle-aged participants as compared to teenagers and young adults. Subjective sleep quality exclusively reflected the shortening of headband-recorded sleep as compared to weekly average TST. REM percent negatively correlated with NREM arousal density. It can be concluded that the overnight REM sleep dynamic (REM maxprop ) is a putative indicator of circadian phase/chronotype with potential relevance for home sleep studies. However, sleep quality indices are less conclusive in between-subjects design, urging the need for longitudinal investigations allowing interindividual analyses.